2015
DOI: 10.5799/ahinjs.01.2015.01.0483
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume and neutrophil to lymphocyte ratio in patients with vernal keratoconjunctivitis

Abstract: Objective: It was aimed to investigate the neutrophil, eosinophil, lymphocyte, platelet count, neutrophil to lymphocyte ratio (NLR) and mean platelet volume (MPV) in patients with vernal keratoconjunctivitis (VKC). Methods:The medical records of the VKC patients who admitted to ophthalmology polyclinic were evaluated. Age and sex matched control group was consisted with patients without any systemic or ocular disease except strabismus. Age and gender of all participants were recorded. Hemogram parameters such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…[11] Oküler hastalıklar sistemik inflamasyondan ziyade lokal bir inflamatuar yanıta neden olmasına rağmen NLO'nun yaşa bağlı makular dejenerasyon, retinal ven tıkanıklığı, non-arteritik anterior iskemik optik nöropati, vernal keratokonjonktivit, kuru göz ve primer açık açılı glokom gibi çeşitli göz hastalıklarında ilişkili olduğu saptanmış-tır. [25][26][27][28][29][30][31] NLO'nun lokal inflamatuar hastalıklarda anlamlı olabilmesi için sistemik kan parametrelerinde değişiklik yapması gerekir. TO'deki inflamasyon aslında sistemik inflamasyonun bir sonucudur ve kan parametrelerini değiştirebilir.…”
Section: Discussionunclassified
“…[11] Oküler hastalıklar sistemik inflamasyondan ziyade lokal bir inflamatuar yanıta neden olmasına rağmen NLO'nun yaşa bağlı makular dejenerasyon, retinal ven tıkanıklığı, non-arteritik anterior iskemik optik nöropati, vernal keratokonjonktivit, kuru göz ve primer açık açılı glokom gibi çeşitli göz hastalıklarında ilişkili olduğu saptanmış-tır. [25][26][27][28][29][30][31] NLO'nun lokal inflamatuar hastalıklarda anlamlı olabilmesi için sistemik kan parametrelerinde değişiklik yapması gerekir. TO'deki inflamasyon aslında sistemik inflamasyonun bir sonucudur ve kan parametrelerini değiştirebilir.…”
Section: Discussionunclassified
“…The fact that NLR was found high in the patients with age-related macular degeneration, diabetic retinopathy, keratoconus, dry eye, glaucoma, non-arteritic anterior ischemic optic neuropathy, retinal vein occlusion and recurrent optic neuritis supports that NLR can be used as a prognostic marker even in the ophthalmological diseases, which have a localized balance with little systemic involvement. [11][12][13][14][15][16][17] Although the abovementioned studies have found that the NLR is high in many eye diseases, there is still no clinical use in ophthalmologic practice as far as we know, because it is a more recently defined entity.…”
Section: Discussionmentioning
confidence: 99%
“…10 Although ocular diseases often cause local inflammation compared to a systemic inflammatory response, the NLR was investigated in various ocular disorders like age-related macular degeneration; retinal vein occlusion; non-arteritic anterior ischemic optic neuropathy; keratoconus; vernal keratoconjonctivitis; dry eye and primary open-angle glaucoma. [11][12][13][14][15][16][17] NLR should change systemic blood parameters to be an important factor in local inflammatory diseases. Although pterygium is thought to have originated from the UV-altered limbal stem cells, recently there have also appeared some hypotheses related to the origin of bone marrow pregnitor cells (BM-PC).…”
mentioning
confidence: 99%
“…We support that vitamin B12-deficient patients have inflammatory conditions and MPV reflects the inflammatory position. Similarly, MPV was found to have a relationship with some inflammatory processes such as coronary ischemia, preeclampsia, ischemic stroke, rheumatoid arthritis, and inflammatory bowel disease [25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%